ANALYSIS OF THE APPLICATION OF CODE-LOCATION POSITIONING IN THE EASTERN DIRECTION OF THE WEST SIBERIAN RAILWAY - Oleg V. Shugaev; Oksana D. Pokrovskaya; Vasily V. Pochetukha; Sergey V. Lemikhov (International Journal of Advanced Studies)
The presented research paper with a scientific bias is devoted to the analysis of the application of the system of code-location positioning of rolling stock on the stretch of the Eastern direction of the West Siberian Railway. The article describes the subject and object of research, includes the sequence of individual stages of research with justification and data processing.  The publication is conditionally divided into 2 parts, the first is devoted to the methodology of research, the description of the research process, input data and a structural description of individual elements of the interval control system. The mathematical apparatus includes statistical methods for processing data adjusted for the current conditions of the experiment. The determination of throughput and processing capacity was carried out using a foreign method and the author's methodology for evaluating the efficiency of the distillation. The conclusion of the first section of the article indicates the need to use the presented mathematical apparatus. The second part of this publication contains the results of research with conclusions.   The uniqueness of the experiment consists in dividing the research part into several separate stages and conducting them for several months on the current stretch of the main line. The first stage of research is devoted to the accuracy of determining the location of rolling stock using a code-location positioning system. The second stage contains an assessment of changes in throughput and carrying capacity on a separate loaded stretch of the Eastern direction of the West Siberian Railway. The final stage of the experiment contains an assessment of the study of the response rate of the proposed motion control system. The results of the research and the summary of the entire work are located in the final part of the publication, which includes analysis and analysis of the experiment. The final section describes recommendations for improving operating conditions using the data obtained and the author's assessment of the effectiveness of the rolling stock code-location positioning system on a separate stretch of the main line section of the Eastern direction of the West Siberian Railway.